Para-fiqh: Bridging Thematic Fiqh to Ushūl and Ushūl’s Response to Specialization of Fiqh - Siregar, Ahmad Sholihin (IAIN Samarinda, 2018)
The latest trend regarding the study of contemporary thematic Islamic jurisprudence (fiqh) is built upon a paradigm that fiqh, as a science developed in the Islamic tradition, is able to respond to every modern challenge. This paradigm seems to be incompatible with the study of the Islamic legal theory (Ushū al-fiqh) which is considered stagnant. However, the study of Ushū al-fiqh is, the initial gate to the discussion of legal reasoning which enables those who master it come up with theoretically correct rulings and hopefully responsive to the needs of the times. Discussing the thematic Islamic jurisprudence (fiqh) without going through the Ushū al-fiqh thinking framework may lead to a serious gap to the product of the thematic fiqh study. The thematic fiqh studies such as fiqh siyāsah (Islamic jurisprudence on constitution), fiqh munākahat (Islamic jurisprudence on marriage), and Islamic jurisprudence on health issues are not infrequently distorted from the actual context. This article offers a way of dealing with the gaps. In this case, the terminology presented is para-fiqh. Para-fiqh is a term to bridge the trend between the thematic fiqh studies and the stagnancy of Ushū al-fiqh study which, in turn, give birth to the antithesis in the form of thematic Ushū al-fiqh. This article employs the conceptual-doctrinal approach which seeks to present the problems of various classical literatures of the Muslim scholars. By scrutinizing the concept para-fiqh, it is hoped that: first, this article presents a universal legal argument on some particular legal themes; second, it explains the principles of Ushū al-fiqh to understand the thematic fiqh products. The findings emphasize that the para-fiqh concept is important for enriching the intellectual tradition of Muslim communities, as well as being a bridge between the gaps created by the study of Islamic jurisprudence (fiqh) and the study of Islamic legal theory (Ushū al-fiqh).Keywords: para-fiqh; thematic ushūl, thematic fiqh, Ushūl jināyat; Ushūl mu`āmalat. AbstrakTrend terbaru mengenai kajian fiqh tematik kontemporer saat ini membangun paradigma bahwa fiqh adalah salah satu ilmu yang berkembang dalam tradisi Islam yang mampu merespon tantangan zaman. Paradigma ini seakan tidak sebangun dengan kajian Ushul fiqh yang dianggap stagnan. Namun demikian, kajian Ushul fiqh sebenarnya adalah gerbang awal pembahasan penalaran hukum sehingga melahirkan keputusan-keputusan hukum yang tepat. Membahas fiqh tematik tanpa melalui kerangka berfikir ushuliy membawa gap yang serius terhadap produk kajian fiqh tematik tersebut. kajian-kajian tematik seperti fiqh siyāsah, fiqh, munākahat, fiqh kontemporer dan kesehatan tidak jarang terserabut dari konteks yang sebenarnya. Artikel ini menawarkan sebuah jalan lintas mengenai gap yang terjadi. Dalam kasus ini, terminology yang dihadirkan adalah para-fikqh. Para-fiqh adalah istilah untuk menjembatani antara trend kajian fiqh tematik dengan stagnasi kajian ushul fiqh; sehingga melahirkan antitesa berupa ushul fiqh tematik. Kajian dalam artikel ini bersifat konseptual-doktrinal yang berusaha menyajikan persoalan dari berbagai pustaka klasik sarjana Muslim. Artikel ini menemukan ada 2 tujuan: pertama, menghadirkan argumen hukum universal pada beberapa tema hukum yang partikular. Kedua, menjelaskan prinsp-prinsip ushūl guna memahami produk fikih tematik. Hasil dari artikel ini menekankan bahwa para-fiqh penting untuk memperkaya khazanah intelektual tradisi intelektual masyarakat Muslim, sekaligus menjadi jembatan penghubung dari gap yang terjadi karena persoalan fiqh dan ushūl fiqh.Kata Kunci: para-fiqh; ushūl tematik, fikih tematik, Ushūl jināyat; Ushūl mu`āmalat.